(untitled) (Comprehensive Journal of Science, 2025)
Fatigue sensors are used as Structural Health Monitoring (SHM) mechanisms to detect damage on struc- tural components before any failures occur. In this study, a U-notched fatigue sensor was designed and analyzed to predict the fatigue life before catastrophic failure occurs. The ANSYS workbench software and 7075-T6 aluminum alloy were used to model and analyze our U-notch type fatigue sensor. The sensor model consisted of four beams of 305 × 76.2 × 1.6 mm (length × width × thickness) dimensions with different fatigue U-notch radii. It was observed that fatigue life increased with an increase in the U-notch radius. However, the value of the maximum equivalent stress decreased with an increase in the notch radius. In addition, fatigue damage occurred around the U-notch radius when the U-notch radius was equal to or less than 6.4 m